PROYEK PENGGUNAAN KEMBALI SAMPAH KARDUS MENJADI BENDA PAKAI UNTUK SATUAN PENDIDIKAN DI KABUPATEN BANGKA - adhe anggry; Shanty Dwi K; Indah Riezky P (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Inorganic waste in the form of cardboard waste can be reused into various recycled creations that have economic value. This service project aims to provide direct benefits from recycling cardboard waste into disposable objects for educational units in Bangka Regency. The cardboard waste recycling method starts from collecting cardboard waste around the Polman Negeri Babel environment and implementing a creation class. The creation class was attended by several students of Mechanical Design Engineering study program. The design of disposable objects is made using AutoDesk Inventor software according to the theme and design form. In making the design, the main thing that must be considered is that the dimensions of the used object must be adjusted to the size of the cardboard that is available or used. The result of this service project is that the UKS Shelf consists of three objects, namely the UKS shelf, first aid kit and file box, each made in 4 copies, so that there are 4 Education Units in Bangka Regency that will benefit directly from this project.